Investigation of tritium atom exchange in plastic liquid scintillation vials - Wang, John Jen-Chiang, author; Brandl, Alexander, advisor; Sudowe, Ralf, committee member; Walrond, John, committee member (Colorado State University. Libraries, 2018)
Tritium is a naturally occurring radionuclide; it is an analyte of interest in many air, soil, and water samples. It has been shown that long term storage and study of tritium samples results in a reduction in tritium activity not attributed to the natural radioactive decay. Several explanations have been offered through past literatures including diffusion, LSC cocktail degradation, and change in quenching effects. Another possible explanation for the decrease in activity is that tritium may have been organically bound to the plastic possibly due to exchangeable hydrogen atoms along the plastic carbon chain. The hypothesis that tritium can be incorporated into the plastic, interchanging the 1H atoms in the plastic with 3H atoms, was experimentally tested. The experiment consisted of adding deionized water into a previously used plastic vial which had contained tritium to determine if the deionized water had now become tritiated. The results showed that the longer the tritiated water is stored in the vials, the greater the loss of tritium activity in plastic vials is compared to glass vials. An increase in the time that the tritiated water is stored also increases the activity of the tritium found in the deionized water in plastic vials but not in the glass vials. The combination of these two observations supports the hypothesis that tritium exchange may have occurred between the tritiated water and the hydrogen within the plastic vials.